2018
DOI: 10.1111/ppa.12869
|View full text |Cite
|
Sign up to set email alerts
|

Distinct strains of the re‐emergent Cassava common mosaic virus (genus: Potexvirus) infecting cassava in Argentina

Abstract: Cassava common mosaic disease (CCMD) has been reported in all regions where cassava is grown in the Americas and the causal agent, Cassava common mosaic virus (CsCMV), has been identified as a mechanically transmitted potexvirus (Alphaflexiviridae). In Argentina, cassava is grown mainly in the northeast (NEA) region that shares borders with Brazil and Paraguay. Increasing incidences of CCMD were observed during the years 2014 to 2016 associated with severe leaf mosaic symptoms and yield reductions where the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 26 publications
1
25
0
2
Order By: Relevance
“…CsCMV was detected by double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) performed in polystyrene microtitre plates with anti-CsCMV-IgG as described Zanini et al (2018). All plants were tested.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…CsCMV was detected by double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) performed in polystyrene microtitre plates with anti-CsCMV-IgG as described Zanini et al (2018). All plants were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Sections were cut with a diamond knife using an ultra-microtome and collected onto nickel grids. For immuno-electron microscopy, sections mounted on nickel grids were preincubated with 1% bovine serum albumin (BSA) in 1% phosphate buffered saline (PBS) overnight, and then treated with specific antiserum anti-CsCMV (Zanini et al 2018) for six hours. The sections were then exposed to gold conjugated protein A of 5 nm in diameter (Zymed, now part of the Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Originally reported to cause significant yield losses in southern Brazil since the 1940s (reviewed in Lozano et al (2017)), recent outbreaks of CCMD have been reported in Peru and Argentina Xing, Hernandez Nopsa et al -17 (Di Feo et al 2015, Zanini et al 2018. Because of the likely spread of these pathogens through asymptomatic planting material, it is probable that patterns of spread throughout Latin America are related to high intensity areas of production.…”
Section: Cassava Frogskin Disease Is An Economically Important Diseasmentioning
confidence: 99%